Knowledge map and hotspot analysis in source appointment of heavy metals from 1994 to 2022: a scientometric review - Jia, Ziyi; Cai, Angzu; Li, Rui; Wang, Xia; Liu, Yuan (Frontiers in Environmental Science, 2024)
In recent decades, more and more studies have been conducted on source appointment of heavy metals, since they can accumulate in the food chain and have a negative impact on the ecological environment and human health. However, almost never before had scholars tried to make a comprehensive and methodical review in this field from the scientometric and bibliometric perspective. The purpose of this review is to offer insights into the research topics and trend evaluation in terms of source appointment of heavy metals over time using the visualization and analysis software, CiteSpace. We retrieved a total of 2,533 articles from the Web of Science Core Collection (WoSCC) dated between 1994 and 2022, and analysed the progress, hotspots, and trends in this field by synthesized networks of cooperation analysis, co-citation analysis, keyword co-occurrence and cluster analysis, and keywords burst analysis. The overall development of the topic can be divided into four periods, and the rapid development began from 2010. Environmental Sciences was the leading subject category, and the journal Science of the Total Environment had the highest number of publications (9.51%), which was most cited as well (2,390 times). China published the most articles in this field, in which Chinese Academy of Sciences was the leading institution. Said Muhammad and Xinwei Lu were the top two most productive authors. According to citation frequency, Hakanson L was the movers and shakers. Keyword co-occurrence and cluster analysis results showed that “the health risk assessment,” “lake sediments”, “trace elements,” “positive matrix factorization,” “air pollution,” “road dust,” and “megacity” are likely to be hotspots. The “particulate matter,” “China,” “sediments” and “road dust” demonstrated the research tendencies of this domain by keyword burst analysis.